Method for preparing monocyclic and polycyclic aromatic hydrocarbons through catalytic hydrogenation depolymerization of lignin
Through the lignin catalytic hydrodepolymerization method under solvent-free conditions, the use of specific catalysts and control conditions has solved the problem of difficulty in efficiently preparing single-cycle and polycyclic aromatic hydrocarbons in the prior art, and achieved efficient and environmentally friendly aromatic hydrocarbon preparation effect.
Patent Information
- Application Number
- CN202411883114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to efficiently prepare high-yield monocyclic and polycyclic aromatic hydrocarbons directly from lignin under solvent-free conditions, and the use of solvents will bring about energy recovery and solvent decomposition problems.
The catalytic hydrogenodisposal method of lignin under solvent-free conditions was adopted, and direct hydrogenodisposal conversion of lignin was achieved by controlling the mass ratio of the catalyst/lignin, reaction temperature, initial hydrogen pressure and reaction time.
It is achieved efficient preparation of monocyclic and polycyclic aromatic hydrocarbons from lignin under solvent-free conditions, avoiding the problems of solvent recovery and increased energy consumption, and catalyst selection optimizes lignin conversion and oil yield.
Smart Images

Figure CN119662308A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing monocyclic and polycyclic aromatic hydrocarbons, and in particular to a method for preparing monocyclic and polycyclic aromatic hydrocarbons by catalytic hydrogenation and depolymerization of lignin under solvent-free conditions. Technical Background
[0002] In recent years, with the extensive use of fossil fuels such as coal and oil, energy and environmental problems have gradually intensified. In order to alleviate the contradiction between the growing energy and material needs of mankind and energy shortages and environmental protection, it is very important to find and utilize a rich renewable resource. As the second largest biomass renewable resource, lignin is produced in nature about 19.5 to 45.5 billion tons of lignin each year, of which about 50 million tons come from papermaking waste. Lignin is increasingly attracting attention because it is rich in resources and contains aromatic structures.
[0003] As important organic chemical raw materials, the preparation of monocyclic aromatic hydrocarbons (MAHs) and polycyclic aromatic hydrocarbons (PAHs) from renewable raw materials is of great significance. A large number of literatures have shown that lignin contains a large number of monocyclic aromatic hydrocarbon structures and polycyclic aromatic hydrocarbon structures. Wang et al. (Wang Y, Hou Y, Wu W, Li H, Ren S, Li J. Polycyclic aromatics observed inenzymatic lignin by spectral characterization and ruthenium ion-catalyzed oxidation. Journal of Agricultural and Food Chemistry, 2021, 69: 12148–12155.) discovered the presence of polycyclic aromatic structures in enzymatic lignin through spectral analysis and ruthenium ion-catalyzed oxidation. They (Wang Y, Hou Y, Li H, Wu W, Ren S, Li J. New insights into the coalification of lignite from lignin: A comparison of their chemical structures. Fuel, 2022, 326: 125017.) also found that lignin and lignite (containing monocyclic and polycyclic aromatic structures) are structurally similar. Then, they (Wang Y, Hou Y, Li H, Wu W, Ren S, Li J. A new structural model of enzymatic lignin with multiringaromatic clusters. ACS Omega, 2022; 7: 18861–18869.) based on the yield,13C NMR characterization, etc., constructed a lignin structure model composed of 1-ring, 2-ring and 3-ring aromatic structures. Wei et al. (Wei J, Sun J, Hou Y, et al. Hydroliquefaction of lignin: Can it generate recycle solvents by itself? Fuel, 2024, 366: 131412.) completely liquefied lignin by direct liquefaction and obtained 28.5wt% of polycyclic aromatic hydrocarbons. Although the above reports show that there are monocyclic and polycyclic aromatic structures in lignin, they still cannot directly obtain high-yield monocyclic and polycyclic aromatic hydrocarbons from lignin. At present, there are some patent reports on the preparation of monocyclic aromatic hydrocarbons from lignin. For example, a Chinese patent (application number 201710052842.5) discloses a method for preparing aromatic compounds by hydrogenating and depolymerizing corn straw lignin using electrocatalytic technology. The method uses electrocatalytic oxidation to degrade the degradation intermediates of lignin in a sodium hydroxide solution, that is, a Pb / PbO2 electrode and a Ni electrode are used to form an electrolytic reaction cell and a lignin alkaline solution is used as an electrolyte solution. The active species (hydroxyl radicals or peroxide anion radicals) generated by the electrolysis of alkaline water on the surface of the anode (Pb / PbO2) oxidize and break some chemical bonds in the lignin, effectively reducing the molecular weight of the lignin. The depolymerized compound intermediates are hydrogenated and reduced by the adsorbed hydrogen atoms generated by the electrolysis of alkaline water on the surface of the cathode (Ni electrode), and finally monocyclic aromatic hydrocarbon products such as toluene, o-xylene, and m-xylene are obtained. A Chinese patent (application number 201711304244.9) discloses a method for producing aromatic hydrocarbons by highly selective catalytic transfer hydrogenation of lignin derivatives. This method uses the most abundant aromatic ether compounds in the lignin structure as raw materials to catalytically deoxidize them and convert them into unsaturated aromatic hydrocarbon liquid fuels. The raw material conversion rate and saturated alkane selectivity can reach more than 94%. A Chinese patent (application number 202310587335.7) discloses a method for coupling power generation by depolymerization of lignin to produce aromatic compounds. This method uses a ternary low eutectic solvent and lignin as anodes, and pentavalent vanadium salts and acids as cathodes to perform electrochemical reactions under mild reaction conditions, while generating clean electricity and degrading lignin into aromatic compounds. A Chinese patent (application number 202410280387.4) discloses a method for direct liquefaction of lignin by catalytic hydrogenation to produce oil. The method uses MoS2, MoO3, Mo2C or FeS2 as a catalyst, hydrogen as a reducing agent, and a hydrogen-donating solvent to hydrogenate and liquefy lignin to produce oil. The method has the characteristics of high lignin conversion rate and high oil yield. The oil containing monocyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons can be further used as a lignin-based circulating solvent for direct hydrogenation and liquefaction of lignin. This patent uses a solvent for hydrogenation and liquefaction of lignin, and there are problems with solvent recovery and increased energy consumption when post-processing the liquefied oil.Compared with the use of solvents, the liquefied oil obtained by catalytic hydrogenation and depolymerization of lignin under solvent-free conditions can be separated by a simple distillation method. In summary, the above papers or patents either cannot obtain high yields of monocyclic and polycyclic aromatic hydrocarbons, or use solvents. Based on this, this patent develops a method for solvent-free lignin catalytic hydrogenation liquefaction conversion, which can directly produce a large amount of monocyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons from lignin. Summary of the invention
[0004] The present invention provides a method for realizing direct hydrogenation depolymerization conversion of lignin under solvent-free conditions. The method directly uses lignin as a raw material, hydrogen as a reducing agent, MoS2, 5% Pd-loaded Pd / C, 5% Ru-loaded Ru / C, 5% Pt-loaded Pt / C, CuZnAl (10:1:9), Raney Ni, Raney Ni+Hβ 25 (10:1), Raney Ni+Hβ 40 (10:1), RaneyNi+Hβ 100 (10:1), Raney Ni+HY 40 (10:1), Raney Ni+HZSM-5(10:1), Raney Ni+ZSM-35(10:1) are used as catalysts, and the direct hydrogenation and depolymerization of lignin is catalyzed to prepare monocyclic and polycyclic aromatic hydrocarbons by controlling the mass ratio of catalyst / lignin raw materials, reaction temperature, initial hydrogen pressure and reaction time. This method is a cheap, green, efficient and renewable production method for direct hydrogenation and depolymerization of lignin.
[0005] To achieve the above objectives, the present invention adopts the following specific technical solutions:
[0006] A method for preparing monocyclic and polycyclic aromatic hydrocarbons by solvent-free lignin catalytic hydrogenation and depolymerization, the method comprising the following specific steps:
[0007] S1: adding lignin raw materials and catalyst into a high-pressure reactor and sealing the reactor;
[0008] S2: remove the air in the reactor of step S1, then fill it with H2, stir it at a given temperature to react, and after the time is reached, quickly cool the reactor to end the reaction;
[0009] S3: Take out the product in the reactor of step S2, treat the solid-liquid mixture with dichloromethane to obtain oil (dichloromethane soluble part), asphaltene and pre-asphaltene (dichloromethane insoluble part but tetrahydrofuran soluble part) and residue (tetrahydrofuran insoluble part, including catalyst).
[0010] In step S1 of the above method, the catalyst is selected from MoS2, 5% Pd-loaded Pd / C, 5% Ru-loaded Ru / C, 5% Pt-loaded Pt / C, CuZnAl (10:1:9), Raney Ni, Raney Ni+Hβ 25 (10:1), Raney Ni+Hβ 40 (10:1), Raney Ni+Hβ 100 (10:1), Raney Ni+HY 40 (10:1), Raney Ni+HZSM-5(10:1), Raney Ni+ZSM-35(10:1).
[0011] In step S1 of the above method, the mass ratio of the catalyst to the lignin raw material is 0.25-1.
[0012] In step S2 of the above method, the pressure of the hydrogen gas charged is 1 MPa to 10 MPa.
[0013] In step S2 of the above method, the reaction temperature is 250°C to 450°C.
[0014] In step S2 of the above method, the reaction time is 1 min to 360 min.
[0015] The principle of the direct hydrogenation and depolymerization method of lignin of the present invention is: first, solid lignin and catalyst are mixed evenly, heated in a hydrogen atmosphere, part of the lignin liquefies itself to produce "autogenous solvent", and then provides solvent for the hydrogenation conversion of lignin; as the reaction temperature continues to rise, the C-O bonds and C-C bonds between the monocyclic aromatic clusters and polycyclic aromatic clusters in the lignin structure break to form free radicals; then, these free radicals are hydrogenated by hydrogen activated by the catalyst to form small molecular compounds. Finally, the lignin is completely hydrogenated and depolymerized to be converted into high-yield monocyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons.
[0016] Compared with the lignin hydrogenation depolymerization in the literature, the method of the present invention has the following advantages: (1) no external solvent is added, thus avoiding the problems caused by the use of solvents (such as recovery energy consumption, solvent decomposition and conversion, etc.); (2) the MoS2 selected by the present invention, 5% Pd-loaded Pd / C, 5% Ru-loaded Ru / C, 5% Pt-loaded Pt / C, CuZnAl (10:1:9), Raney Ni, Raney Ni+Hβ 25 (10:1), Raney Ni+Hβ 40 (10:1), Raney Ni+Hβ 100 (10:1), Raney Ni+HY 40(10:1), Raney Ni+HZSM-5(10:1), and Raney Ni+ZSM-35(10:1) catalysts have good catalytic effects, high lignin conversion rates, and high oil yields. The oil contains a large amount of monocyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons; (3) Using renewable biomass lignin as a raw material to prepare monocyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons belongs to the renewable aromatic hydrocarbon preparation technology. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is the GC-MS spectrum of the lignin liquefied oil after hydrogenation and depolymerization in Example 7. DETAILED DESCRIPTION
[0017] The present invention is further illustrated by the following examples, but the protection scope of the present invention is not limited to the following examples.
[0018] The products of direct hydrogenation depolymerization of lignin are processed as follows:
[0019] The solid-liquid mixture after the reaction is treated by Soxhlet extraction using dichloromethane and tetrahydrofuran. The dichloromethane soluble portion is defined as oil, the dichloromethane insoluble tetrahydrofuran soluble portion is defined as asphaltene and pre-asphaltene (PAA for short), and the conversion rate of lignin is: 100% - the mass percentage of the tetrahydrofuran insoluble portion and the lignin.
[0020] After the direct hydrogenation and depolymerization reaction of lignin in the autoclave was completed, the gas was collected in an aluminum foil gas sampling bag, and the combustible hydrocarbons and CO, CO2 small molecule gases in the gas product were determined by GC-FID and GC-TCD. The GC-FID used was produced by Agilent Technologies (model 7820A). The detector was a hydrogen ion flame detector, the chromatographic column was a J&W GSBP capillary column, the injection port temperature was 200°C, the column temperature was 80°C, maintained for 20 minutes, and the detector temperature was 250°C. The GC-TCD used was produced by Agilent Technologies (model 7890A). The detector was a thermal conductivity detector, the chromatographic column was a Supelco 6ft PQ + 6ft 13X packed column, the injection port temperature was 120°C, the column box was maintained at an initial temperature of 50°C for 18 minutes, and the TCD detector temperature was 200°C.
[0021] The solid-liquid mixture after the reaction is all added to a Soxhlet extraction apparatus for dichloromethane extraction to obtain a dichloromethane soluble portion and a dichloromethane insoluble portion. The obtained dichloromethane insoluble portion is then added to a Soxhlet extraction apparatus for tetrahydrofuran extraction to obtain a dichloromethane insoluble but tetrahydrofuran soluble portion and a tetrahydrofuran insoluble portion. The dichloromethane soluble portion is rotary evaporated at 43°C to remove dichloromethane until no more liquid is evaporated, and the volume is fixed and samples are taken for gas chromatography and gas chromatography-mass spectrometry analysis of the composition. The gas chromatograph (GC) and gas chromatograph-mass spectrometer (GC-MS) used are produced by Shimadzu Corporation of Japan (model GC-2014) and Agilent Technologies (7890B / 5977A), respectively. The detector was a hydrogen ion flame detector, the chromatographic column was an HP-5 capillary column, the injection port temperature was 280°C, the initial column box temperature was 45°C, maintained for 3 min, then increased to 105°C at 10°C / min, then increased to 210°C at 5°C / min, and finally increased to 300°C at 10°C / min and maintained for 21 min.
[0022] The oxygen content in oil was determined using the Vario EL cube-O model (GmbH) method.
[0023] Example 1
[0024] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to keep the initial reaction pressure at 8.0MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 250°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0025] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 61%, the oil yield was 30wt%, the PAA yield was 31wt%, the GC detectable product yield was 2.1wt%, the monocyclic aromatic hydrocarbon product yield was 0.13wt%, the polycyclic aromatic hydrocarbon product yield was 0.26wt%, and the oxygen content in the oil was 47.8%.
[0026] Example 2
[0027] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 300°C, the timing began. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0028] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 58wt%, the PAA yield was 21wt%, the GC detectable product yield was 12.3wt%, the monocyclic aromatic hydrocarbon product yield was 0.5wt%, the polycyclic aromatic hydrocarbon product yield was 4.9wt%, and the oxygen content in the oil was 21.8%.
[0029] Example 3
[0030] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 350°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0031] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 76wt%, the PAA yield was 6wt%, the GC detectable product yield was 21.2wt%, the monocyclic aromatic hydrocarbon product yield was 3.7wt%, the polycyclic aromatic hydrocarbon product yield was 7.1wt%, and the oxygen content in the oil was 12.8%.
[0032] Example 4
[0033] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 390°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0034] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 81wt%, the PAA yield was 0wt%, the GC detectable product yield was 37wt%, the monocyclic aromatic hydrocarbon product yield was 10.3wt%, the polycyclic aromatic hydrocarbon product yield was 13.8wt%, and the oxygen content in the oil was 15.3%.
[0035] Example 5
[0036] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 410°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0037] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 69wt%, the PAA yield was 0wt%, the GC detectable product yield was 63.3wt%, the monocyclic aromatic hydrocarbon product yield was 17.3wt%, the polycyclic aromatic hydrocarbon product yield was 35wt%, and the oxygen content in the oil was 5.6%.
[0038] Example 6
[0039] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 430°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0040] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 63wt%, the PAA yield was 0wt%, the GC detectable product yield was 65.4wt%, the monocyclic aromatic hydrocarbon product yield was 18.5wt%, the polycyclic aromatic hydrocarbon product yield was 39.4wt%, and the oxygen content in the oil was 3.7%.
[0041] Example 7
[0042] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0043] Taking this embodiment as an example, the gas chromatography mass spectrum of the product oil is shown in Figure 1 It should be noted that in addition to the compound structures marked in the figure, there are other types of compounds, such as alkanes and cycloalkanes.
[0044] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 62wt%, the PAA yield was 0wt%, the GC detectable product yield was 60.8wt%, the monocyclic aromatic hydrocarbon product yield was 16.7wt%, the polycyclic aromatic hydrocarbon product yield was 40.4wt%, and the oxygen content in the oil was 1.6%.
[0045] Example 8
[0046] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 1MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0047] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 56%, the oil yield was 26wt%, the PAA yield was 25wt%, the GC detectable product yield was 16wt%, the monocyclic aromatic hydrocarbon product yield was 8wt%, the polycyclic aromatic hydrocarbon product yield was 19wt%, and the oxygen content in the oil was 2.9%.
[0048] Example 9
[0049] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 4MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0050] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 56wt%, the PAA yield was 6wt%, the GC detectable product yield was 41wt%, the monocyclic aromatic hydrocarbon product yield was 12.1wt%, the polycyclic aromatic hydrocarbon product yield was 27.5wt%, and the oxygen content in the oil was 2.7%.
[0051] Example 10
[0052] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 6MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0053] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 58wt%, the PAA yield was 0.5wt%, the GC detectable product yield was 57wt%, the monocyclic aromatic hydrocarbon product yield was 15.6wt%, the polycyclic aromatic hydrocarbon product yield was 38.9wt%, and the oxygen content in the oil was 1.6%.
[0054] Embodiment 11
[0055] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 10MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0056] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 62wt%, the PAA yield was 0wt%, the GC detectable product yield was 60wt%, the monocyclic aromatic hydrocarbon product yield was 19.4wt%, the polycyclic aromatic hydrocarbon product yield was 37wt%, and the oxygen content in the oil was 1.5%.
[0057] Example 12
[0058] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 1min of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0059] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 84wt%, the PAA yield was 5wt%, the GC detectable product yield was 41wt%, the monocyclic aromatic hydrocarbon product yield was 14.1wt%, the polycyclic aromatic hydrocarbon product yield was 8.3wt%, and the oxygen content in the oil was 24.4%.
[0060] Embodiment 13
[0061] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 120 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0062] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 66wt%, the PAA yield was 4wt%, the GC detectable product yield was 61wt%, the monocyclic aromatic hydrocarbon product yield was 16.2wt%, the polycyclic aromatic hydrocarbon product yield was 39.3wt%, and the oxygen content in the oil was 12.3%.
[0063] Embodiment 14
[0064] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 360 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0065] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 50wt%, the PAA yield was 6wt%, the GC detectable product yield was 50wt%, the monocyclic aromatic hydrocarbon product yield was 15.6wt%, the polycyclic aromatic hydrocarbon product yield was 31.9wt%, and the oxygen content in the oil was 0.5%.
[0066] Embodiment 15
[0067] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 0.5g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0068] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 47wt%, the PAA yield was 14wt%, the GC detectable product yield was 12.7wt%, the monocyclic aromatic hydrocarbon product yield was 3.6wt%, the polycyclic aromatic hydrocarbon product yield was 8.4wt%, and the oxygen content in the oil was 41.2%.
[0069] Example 16
[0070] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 1g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0071] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 55wt%, the PAA yield was 5wt%, the GC detectable product yield was 14wt%, the monocyclic aromatic hydrocarbon product yield was 5wt%, the polycyclic aromatic hydrocarbon product yield was 8.3wt%, and the oxygen content in the oil was 5.5%.
[0072] Embodiment 17
[0073] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 1.5g of MoS2 catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0074] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 100%, the oil yield was 58wt%, the PAA yield was 3wt%, the GC detectable product yield was 17wt%, the monocyclic aromatic hydrocarbon product yield was 5.9wt%, the polycyclic aromatic hydrocarbon product yield was 11.1wt%, and the oxygen content in the oil was 3.6%.
[0075] Embodiment 18
[0076] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3The reaction was carried out in a high-temperature and high-pressure reactor. 2 g of lignin and 2 g of 5% Pd-loaded Pd / C catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; subsequently, N2 with a pressure of 8 MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1 MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8 MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. After the reactor cooled to room temperature, samples were collected for analysis.
[0077] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 98%, the oil yield was 53wt%, the PAA yield was 0wt%, the GC detectable product yield was 51wt%, the monocyclic aromatic hydrocarbon product yield was 14wt%, the polycyclic aromatic hydrocarbon product yield was 33wt%, and the oxygen content in the oil was 2.8%.
[0078] Embodiment 19
[0079] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2 g of lignin and 2 g of 5% Ru-loaded Ru / C catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; subsequently, N2 at a pressure of 8 MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1 MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8 MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. After the reactor cooled to room temperature, samples were collected for analysis.
[0080] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 97%, the oil yield was 54wt%, the PAA yield was 0wt%, the GC detectable product yield was 50wt%, the monocyclic aromatic hydrocarbon product yield was 12wt%, the polycyclic aromatic hydrocarbon product yield was 34wt%, and the oxygen content in the oil was 2.9%.
[0081] Embodiment 20
[0082] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2 g of lignin and 2 g of 5% Pt-loaded Pt / C catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; subsequently, N2 with a pressure of 8 MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1 MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8 MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. After the reactor cooled to room temperature, samples were collected for analysis.
[0083] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 98%, the oil yield was 57wt%, the PAA yield was 0wt%, the GC detectable product yield was 55wt%, the monocyclic aromatic hydrocarbon product yield was 15wt%, the polycyclic aromatic hydrocarbon product yield was 34wt%, and the oxygen content in the oil was 2.7%.
[0084] Embodiment 21
[0085] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of CuZnAl catalyst (10:1:9) were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0086] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 98%, the oil yield was 58wt%, the PAA yield was 0wt%, the GC detectable product yield was 56wt%, the monocyclic aromatic hydrocarbon product yield was 14wt%, the polycyclic aromatic hydrocarbon product yield was 36wt%, and the oxygen content in the oil was 2.9%.
[0087] Embodiment 22
[0088] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of Raney Ni catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirring was turned on. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0089] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 96%, the oil yield was 56wt%, the PAA yield was 0wt%, the GC detectable product yield was 54wt%, the monocyclic aromatic hydrocarbon product yield was 15wt%, the polycyclic aromatic hydrocarbon product yield was 37wt%, and the oxygen content in the oil was 3.1%.
[0090] Embodiment 23
[0091] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 2g of lignin and 2g of Raney Ni+Hβ 25The (10:1) catalyst was added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0092] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 97%, the oil yield was 57wt%, the PAA yield was 0wt%, the GC detectable product yield was 55wt%, the monocyclic aromatic hydrocarbon product yield was 16wt%, the polycyclic aromatic hydrocarbon product yield was 35wt%, and the oxygen content in the oil was 2.9%.
[0093] Embodiment 24
[0094] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 2g of lignin and 2g of Raney Ni+Hβ 40 The (10:1) catalyst was added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0095] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 98%, the oil yield was 55wt%, the PAA yield was 0wt%, the GC detectable product yield was 53wt%, the monocyclic aromatic hydrocarbon product yield was 14wt%, the polycyclic aromatic hydrocarbon product yield was 35wt%, and the oxygen content in the oil was 2.8%.
[0096] Embodiment 25
[0097] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 2g of lignin and 2g of Raney Ni+Hβ 100 The (10:1) catalyst was added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0098] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 95%, the oil yield was 57wt%, the PAA yield was 0wt%, the GC detectable product yield was 56wt%, the monocyclic aromatic hydrocarbon product yield was 15wt%, the polycyclic aromatic hydrocarbon product yield was 36wt%, and the oxygen content in the oil was 3.1%.
[0099] Embodiment 26
[0100] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 2g of lignin and 2g of Raney Ni+HY 40 The (10:1) catalyst was added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0101] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 96%, the oil yield was 58wt%, the PAA yield was 0wt%, the GC detectable product yield was 54wt%, the monocyclic aromatic hydrocarbon product yield was 14wt%, the polycyclic aromatic hydrocarbon product yield was 36wt%, and the oxygen content in the oil was 2.9%.
[0102] Embodiment 27
[0103] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3 The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of Raney Ni+HZSM-5 (10:1) catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. After the reactor cooled to room temperature, samples were collected for analysis.
[0104] The analysis results show that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 97%, the oil yield was 54wt%, the PAA yield was 0wt%, the GC detectable product yield was 50wt%, the monocyclic aromatic hydrocarbon product yield was 15wt%, the polycyclic aromatic hydrocarbon product yield was 34wt%, and the oxygen content in the oil was 2.9%.
[0105] Embodiment 28
[0106] The direct hydrogenation depolymerization test of lignin in this example was carried out under the conditions of using lignin as raw material and hydrogen as reducing agent. 3The reaction was carried out in a high-temperature and high-pressure reactor. 2g of lignin and 2g of Raney Ni+ZSM-35 (10:1) catalyst were added to the reactor, the reactor was sealed, nitrogen (N2) was introduced and purged three times to remove air from the system; then, N2 with a pressure of 8MPa was introduced for leak detection. Half an hour later, the pressure change in N2 was less than 0.1MPa, indicating that the high-temperature and high-pressure reactor was airtight. After that, hydrogen (H2) was introduced and purged three times in sequence to remove the residual N2 in the high-temperature and high-pressure reactor; finally, H2 was added to maintain the initial reaction pressure of 8MPa. The reactor was placed in a heating jacket and stirred. When the reaction temperature reached 450°C, the timing was started. After 240 minutes of reaction, the reactor was taken out and cooled with a blower to terminate the reaction. When the reactor cooled to room temperature, samples were collected for analysis.
[0107] The analysis results showed that during the direct hydrogenation and depolymerization test of lignin, the lignin conversion rate was 95%, the oil yield was 55wt%, the PAA yield was 0wt%, the GC detectable product yield was 51wt%, the monocyclic aromatic hydrocarbon product yield was 16wt%, the polycyclic aromatic hydrocarbon product yield was 33wt%, and the oxygen content in the oil was 3.1%.
Claims
1. A method for preparing monocyclic and polycyclic aromatic hydrocarbons by catalytic hydrogenation and depolymerization of lignin, the method comprising the following specific steps: S1: adding lignin raw materials and catalyst into a high-pressure reactor and sealing the reactor; S2: removing the air in the reactor of step S1, then filling it with H2, stirring at a given temperature to carry out catalytic hydrogenation reaction, and after the time is reached, quickly cooling the reactor to terminate the reaction; S3: taking out the product in the reaction kettle of step S2, treating the solid-liquid mixture with dichloromethane to obtain oil (dichloromethane soluble portion), asphaltene and pre-asphaltene (dichloromethane insoluble portion but tetrahydrofuran soluble portion) and residue (tetrahydrofuran insoluble portion, including catalyst); In the above step S1, the catalyst is selected from MoS2, 5% Pd-loaded Pd / C, 5% Ru-loaded Ru / C, 5% Pt-loaded Pt / C, CuZnAl (10:1:9), Raney Ni, Raney Ni+Hβ 25 (10:1), Raney Ni+Hβ 40 (10:1), RaneyNi+Hβ 100 (10:1), Raney Ni+HY 40 (10:1), Raney Ni+HZSM-5, Raney Ni+ZSM-35(10:1).
2. The method according to claim 1, characterized in that In step S1, the mass ratio of the catalyst to the lignin raw material is 0.25-1.
3. The method according to claim 1, characterized in that The pressure of hydrogen filled in step S2 is 1 MPa to 10 MPa.
4. The method according to claim 1, characterized in that: The reaction temperature in step S2 is 250°C to 450°C.
5. The method according to claim 1, characterized in that The reaction time in step S2 is 1 min to 360 min.
Citation Information
Patent Citations
Method for preparing aromatic compounds by conducting hydrogenation and depolymerization on spruce lignin through electro-catalysis technology
CN106676574A
A method for producing aromatics by highly selective catalytic transfer hydrogenation of lignin derivatives
CN108048125B
Coupling power generation method for preparing aromatic compound through lignin depolymerization
CN116791106A
Method for preparing oil through catalytic hydrogenation and direct liquefaction of lignin
CN117925265A